Evaluating Surveillance Breast Imaging and Biopsy in Older Breast Cancer Survivors - Tracy Onega; Julie Weiss; Roberta diFlorio; Todd MacKenzie; Martha Goodrich; Steven Poplack (International Journal of Breast Cancer)
Background. Patterns of surveillance among breast cancer survivors are not well characterized and lack evidence-based practice guidelines, particularly for imaging modalities other than mammography. We characterized breast imaging and related biopsy longitudinally among breast cancer survivors in relation to women’s characteristics. Methods. Using data from a state-wide (New Hampshire) breast cancer screening registry linked to Medicare claims, we examined use of mammography, ultrasound (US), magnetic resonance imaging (MRI), and biopsy among breast cancer survivors. We used generalized estimating equations (GEE) to model associations of breast surveillance with women’s characteristics. Results. The proportion of women with mammography was high over the follow-up period (81.5% at 78 months), but use of US or MRI was much lower (8.0%—first follow-up window, 4.7% by 78 months). Biopsy use was consistent throughout surveillance periods (7.4%–9.4%). Surveillance was lower among older women and for those with a higher stage of diagnosis. Primary therapy was significantly associated with greater likelihood of breast surveillance. Conclusions. Breast cancer surveillance patterns for mammography, US, MRI, and related biopsy seem to be associated with age, stage, and treatment, but need a larger evidence-base for clinical recommendations.